MODEL PEMBELAJARAN HYBRIT LEARNING PADA MATA KULIAH SEPAKBOLA DI PENDIDIKAN OLAHRAGA FKIP UMS - indarto, pungki (Journal of Sport Science and Education, 2018)
1). The hybrid learning model is the process of learning which is the mixture of face to face and on line learning models. 2). Theadvancement of the learning result and the mastery of skills on the soccer lecture series in the faculty of education and teacher training of UMS. 3). The students enthusiasm in takingthe lecture series using the hybrid learning in in the faculty of education and teacher training of UMS. The method of research applies the steps of Borg and Gall up to the seventh steps in small scale.Data is taken from the questionnaires and tests. Data analysis is inthe form of descriptive and the product effectively tests. From the result of the research, it can be concluded that Hybrid learning is suitable to be applied in the lecture series of soccer in the faculty of education and teacher training of UMS.The Hybrid learningmethod is able to increase the achievement of the students from the average score of 6.8 with the total score of 204before applying the method, and after applying the learning media the score increase to 7.53 with the total score of225.8. There is a variance from the pretest and posttest as much as 0.73 point. So it can be concluded that there is an increase in the use of hybrid learning in the soccer lecture seriesin the faculty of eduation and teacher training of UMS.